Implementation of the Smart Economy Concept in Balikpapan City - Hasibuan, Tio Bennetsia; Aziza Gaffar, Emmilya Umma (INOVASI: Jurnal Ekonomi, Keuangan, dan Manajemen, 2025)
Smart Economy It is a concept of urban management innovation that is able to face economic competition in creating business opportunities, utilizing existing resources efficiently and improving the city's economy. This research aims to identify the implementation of the concept of Smart Economy through 6 indicators, namely economic growth in the leading sector, business licensing Online, small industry centers, MSMEs that are integrated with e-marketplace, a creative populist economy and a cashless. The data used in this study are secondary data and primary data with descriptive analysis methods. Based on the results of the analysis, it shows that the concept of Smart Economy has not been fully implemented and is still in the monitoring stage, but the researcher concluded that there are obstacles in the research, namely the completeness of data and the existence of obstacles in several programs so that further studies, government and private support are needed to maximize the concept Smart Economy towards Smart City in Balikpapan City